2010
DOI: 10.1590/s1517-83822010000200008
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal susceptibility profile of Trichosporon isolates: correlation between CLSI and etest methodologies

Abstract: The aim of the present study was to evaluate the antifungal susceptibility profile of Trichosporon species isolated from different sources employing the Clinical and Laboratory Standards Institute (CLSI) method and E-test method. Thirty-four isolates of Trichosporon spp. and six CBS reference samples were tested for their susceptibility to Amphotericin B, 5-flucytosine, Fluconazole, Itraconazole, Voriconazole and Terbinafine. All species showed high Minimun Inhibitory Concentrations (MIC) for Itraconazole and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
2
9
1
Order By: Relevance
“…Amphotericin B and Chloramphenicol (Sigma Chemical Co.) were used as the reference antimycotic and antibacterial controls, respectively, on the basis of their use as reference antimicrobial compounds in bioassays with crude medicinal plant extracts (2, 7, 14, 17, 20, 25). …”
Section: Methodsmentioning
confidence: 99%
“…Amphotericin B and Chloramphenicol (Sigma Chemical Co.) were used as the reference antimycotic and antibacterial controls, respectively, on the basis of their use as reference antimicrobial compounds in bioassays with crude medicinal plant extracts (2, 7, 14, 17, 20, 25). …”
Section: Methodsmentioning
confidence: 99%
“…However, from 2010 onward the first sporadic cases of Trichosporon spp . resistant to voriconazole were reported [ 9 , 10 ], and a recent study from Greece reported that 38 % of Trichosporon isolates had a MIC ≄ 2 mg/L for voriconazole [ 11 ]. Most of these strains were susceptible to at least one other triazole, and treatment failures were not described in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, it was used the broth microdilution method in conformity with CLSI, and the readings were performed by Anthos Zenyth 200rt Microplate Reader with filter at a wavelength of 530 nm (LEMES et al, 2010). As a result, two T. asahii strains have exhibited MIC of 250 ÎŒg mL ) were similar to those values found by Asamenew et al (2011) with the same standard strain (400 ÎŒg mL -1 ); in addition, these scientists also observed the antimicrobial action of A. harlana latex on several bacteria and some fungi.…”
Section: Resultsmentioning
confidence: 99%
“…However, serious infections caused by Trichosporon asahii, once described as limited to immunocompromised, oncologic and hematologic patients, have been frequently reported in elderly patients with severe heart failure, thereby leading to an increase in the death rate of such patients hospitalized at ICU (LEMES et al, 2010). Consequently, the increasing morbidity and mortality by fungal infections, particularly those caused by Trichosporon genus yeasts, has led to the interest of developing more efficient antimycotic therapies.…”
Section: Introductionmentioning
confidence: 99%